Advancing the Taxonomy of the Diatom Pseudo-nitzschia Through an Integrative Study Conducted in the Central and Southeastern Adriatic Sea - Tina Bonačić; Jasna Arapov; Ivana Bušelić; Ivana Lepen Pleić; Blanka Milić Roje; Tina Tomašević; Mia Bužančić; Marija Mladinić; Silvia Casabianca; Antonella Penna; Sanda Skejić; Živana Ninčević Gladan (Plants)
The marine diatom genus Pseudo-nitzschia comprises cosmopolitan phytoplankton species commonly present in the Adriatic Sea. Species within the genus Pseudo-nitzschia have been of significant concern because they produce domoic acid (DA), which can cause amnesic shellfish poisoning (ASP). In this study, we identified Pseudo-nitzschia species along the Central and Southeastern Adriatic Sea, where monthly sampling carried out from February 2022 to February 2024 allowed for comprehensive species documentation. Pseudo-nitzschia species cell cultures isolated from the study areas were morphologically and molecularly analysed. Morphological analyses were performed using a scanning electron microscope (FE-SEM/STEM), while molecular analyses were conducted, targeting the ITS1-5.8S-ITS2, LSU, and rbcL regions, to confirm species identity. This integrative approach led to the identification of eight species: Pseudo-nitzschia allochrona, Pseudo-nitzschia calliantha, Pseudo-nitzschia delicatissima, Pseudo-nitzschia fraudulenta, Pseudo-nitzschia mannii, Pseudo-nitzschia multistriata, Pseudo-nitzschia pseudodelicatissima, and Pseudo-nitzschia subfraudulenta. Our findings underscore the value of a combined approach for reliable species identification and contribute to the development of genetic sequence databases that support the advancement of next-generation methods such as metabarcoding. This research emphasises the importance of combined morphological and molecular methods for the differentiation of the cryptic and pseudo-cryptic Pseudo-nitzschia species.